The Dependence of Edible Grape Variety Kattakurgon on The Growth Indicators and The Biochemical Composition of Grape Juice (Eurasian Journal of Research, Development and Innovation, 2021)
The scientific article provides experimental material devoted to the study of the dependence of the prolificness of shoots and the biochemical composition of grapes of the Kattakurgan variety on the loads of the vine canes. The experiment studied the loads of the vine canes: 80-120, 120-160, 160-200, 200-240 and 240-280 pieces It was found that when the bushes are loaded at the rate of 160-200 eyes in each bush, the number of fruitful shoots develops by 2.7 pieces more than in the control variant in a freely growing culture. At the same time, in the optimal variant of the experiment, the sugar content in the berries was 22.5%, the acidity of the juice was 3 g/l.